The Influence of Visa-on-Arrival and Digital Nomad Policies on Local Economic Growth: A Study on Super Priority Tourism Destinations in Post-G20 Indonesia - Aulia Maharani (Al-Makki Publisher, 2023)
Indonesia's G20 Presidency in 2022 was followed by a breakthrough policy to expand Visa-on-Arrival (VoA) and was taken advantage of by the global digital nomad wave. This phenomenon has the potential to be a catalyst for economic recovery, especially in Super Priority Tourism Destinations, but its empirical impact has not been measured. This study aims to analyze the influence of VoA and digital nomad policies on local economic growth, map their contributions, and evaluate their effectiveness in post-G20 priority destinations. The study uses a mixed-methods approach with a sequential explanatory design. Quantitative data (questionnaires, BPS time series data) were analyzed statistically descriptive and inferential, while qualitative data (interviews, FGDs) were analyzed thematically. The study was conducted in five Super Priority Destinations. The VoA policy contributed significantly to the recovery of tourist visits (+250.6% yoy, 2022), but the impact was uneven and concentrated in destinations with mature infrastructure such as Bali. Digital nomads contribute 2.8 times more than ordinary tourists with unique spending patterns (long-term rentals, co-working spaces, daily necessities), creating a steady economic flow but fueling gentrification challenges. There is a positive synergy between VoA and digital nomads in boosting the local economy. For inclusive and sustainable growth, policy interventions such as special digital nomad visas, MSME liaison programs, and gentrification mitigation regulations are needed. The implications of the findings are the basis for strategic policy recommendations for stakeholders.